The Tendency of Eco-Brick Uses in Bangladesh: Current Trends and Future Needs (International Journal of Sustainable Rural Development, 2024)
This study examined the inclination of microentrepreneurs (MEs) to utilize and engage in commerce with environmentally friendly construction materials as opposed to conventional bricks. The propensity was explored using focus group discussions and key informant interviews. The research region underwent a total of eight Key Informant Interviews (KIIs) and four Focus Group Discussions (FGDs). Nevertheless, the survey revealed that a small number of microentrepreneurs have a fundamental understanding of the environment and pollution. A significant proportion of the MEs failed to implement waste management effectively. The study also discovered that a minuscule proportion of MEs engage in ecologically sustainable production and advertising strategies. All brick kilns utilized topsoil as the primary material for manufacturing conventional fired bricks, employing firewood as the fuel source. They lacked sufficient expertise in utilizing fly ash as a component in the production of bricks and other construction materials. Furthermore, the level of women’s involvement in these firms was exceedingly minimal, and they receive comparably meager remuneration from those enterprises. Enterprises should prioritize creating a supportive environment for women and implementing fair wage policies that result in improved compensation for female employees. A significant proportion of the microentrepreneurs (MEs) lacked training and failed to adhere to adequate safety protocols. Consequently, it is imperative to prioritize training programs focused on safety and security for both workers and microentrepreneurs.